DENOTASI DAN KONOTASI PADA UNGGAHAN MEME AKUN INSTAGRAM @MEKDIUNM: KAJIAN SEMIOTIKA BARTHES - Bintara, Paksi Jaladara; Suriadi, Suriadi (Universitas Negeri Makassar, 2025)
This research aims to reveal the denotation and connotation meanings of @mekdiunm Instagram account memes with Roland Barthes' semiotic approach. The research method used is descriptive qualitative with data sources in the form of several @mekdiunm Instagram account memes. The data collection techniques are listening and recording, while the data analysis techniques include; 1) reading data; 2) analyzing data; 3) describing and discussing the results of the analysis, and; 4) making conclusions. The results show that denotation meaning can be directly understood, while connotation meaning needs to understand certain contexts first.